1999
DOI: 10.1063/1.124181
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced liquid crystal alignment based on a surface relief grating in an assembled cell

Abstract: Surface relief gratings have been optically inscribed on azopolymer films on the interior surface of an empty liquid crystal (LC) cell. Uniform LC alignment is observed in the inscribed regions when the cell is filled. Since the microgrooves are on both sides, this may provide a higher degree of order than other techniques. The stability of the relief gratings and the transmittance of the azopolymer films can be further improved by photobleaching. This alignment technique could have useful applications in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 18 publications
0
55
0
2
Order By: Relevance
“…Photoinduced surface relief gratings in a photopolymer are attractive for their applications in diffractive optical elements [1,2], optical data storage [3], recording computer generated holograms [4] and the alignment of liquid crystals [5][6][7][8]. There has been extensive growth of technological applications of liquid crystals, such as photonic components and liquid crystal displays (LCDs) in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoinduced surface relief gratings in a photopolymer are attractive for their applications in diffractive optical elements [1,2], optical data storage [3], recording computer generated holograms [4] and the alignment of liquid crystals [5][6][7][8]. There has been extensive growth of technological applications of liquid crystals, such as photonic components and liquid crystal displays (LCDs) in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is often called surface relief amplitudemodulation. Light-induced SRGs in a photopolymer have the potential to align LCs [5][6][7][8]. So, it is important to investigate the mechanism of the formation of surface relief gratings depending on recording parameters and physical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Li and coworkers reported that the PSR structure can tightly anchor the liquid crystal (LC) molecules, and the stability and the transmittance of the PSR/LC assembly could be improved by photobleaching. It is also proposed that this alignment method can be applied to create an in-plane switching device [133][134][135]. Quantitative examination of the anchoring force associated with the PSR structure has been presented by Chung and coworkers [136].…”
Section: Applicationsmentioning
confidence: 99%
“…They are used in the mass production of holograms for applications related with security purposes and holographic-based memories [1] in addition to other applications [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%